Gallic acid protects intervertebral disc cells from ferroptosis and alleviates intervertebral disc degeneration by regulating key factors of oxidative stress - Zhu, Zaishi; Huang, Zeling; Zhang, Chaofeng; Xu, Bo; Chen, Hua; Pei, Shuai; Zhang, Baofei; Jie, Lishi; Shi, Xiaoqing; Liu, Yujiang; Li, Yuwei; Shen, Xiaofeng (Frontiers in Pharmacology, 2025)
BackgroundIntervertebral disc degeneration (IDD) is a chronic degenerative disease and one of the main causes of low back pain (LBP). Currently, there is no effective treatment. Ferroptosis is a cell-regulated process that depends on iron deposition and lipid peroxidation. Inhibiting ferroptosis in nucleus pulposus cells is considered a potential strategy for the treatment of IDD. Gallic acid (GA) is naturally present in a variety of plants and has anti-inflammatory, antioxidant and analgesic effects. It has been shown to alleviate ferroptosis. However, the role of GA in IDD ferroptosis remains unclear.MethodsThis study explored the pathological mechanism of GA in IDD in relation to ferroptosis: (1) to identify ferroptosis-related targets for GA treatment of IDD using network pharmacology and molecular docking technology, (2) to evaluate the therapeutic effect of GA in an IDD rat model and changes in ferroptosis-related targets, (3) to investigate the changes of oxidative stress and lipid peroxidation products in NP cells after GA intervention, and (4) to study the changes of ferroptosis-related proteins and iron ions in cells and mitochondria after GA intervention.ResultsExperimental results confirmed that GA can treat IDD by reducing the degradation of extracellular matrix (ECM) and pathological changes in IDD. GA can also mitigate ferroptosis by reducing oxidative stress and lipid peroxidation in rat nucleus pulposus (NP) cells.ConclusionThe alleviation of disc degeneration ferroptosis by GA may be closely associated with the key ferroptosis proteins P53 and NRF2.